The Effect of Ear Acupuncture Therapy with a Combination of Gotu Kola Tea on Changes in Blood Pressure in Hypertension Cases in Kemandungan Village, Tegal Barat Subdistrict, Tegal City - Darojatin, Ibnati Ulya; Wardoyo, Suwaji Handaru; Sholihah, Imrok Atus (HAKTI : Indonesian Acupuncture Therapists Association, 2024)
Hypertension is high blood pressure with systolic values above 140 mmHg and diastolic values above 90 mmHg. Ear acupuncture and gotu kola tea are nonpharmacological treatments that can be used to treat hypertension. The purpose of this study was to determine the effect of ear acupuncture therapy with a combination of gotu kola tea on changes in blood pressure in cases of hypertension in Kemandungan Village, Tegal Barat Subdistrict, Tegal City. This study used a research design